Seasonal Loading Impact on Performance of Solar DG for Loss Reduction Based on Capacity Factor. (2016) - Sharma, Ritu; Gupta, Atma Ram
Abstract: This paper proposed a methodology to study the seasonal impact on the performance of solar based Distributed Generator (DG) for loss reduction as a main objective. The random behavior of solar irradiance is modeled using beta probability density functions. IEEE RTS (Reliability Test System) data is used for load modeling. Different modules of solar have been studied and appropriate selection is made using capacity factor approach and VSI method is used for finding the optimum location for placement of SPV (Solar Photo Voltaic). An iterative forward backward/BIBC load flow method is used for analysis. The proposed technique has been applied to IEEE 33, IEEE 69 and IEEE 12 bus system and significant reduction of active power losses has been achieved for different seasons of the year.